Frequency of 17p Deletion in Chronic Lymphocytic Leukemia Patients Presenting to Combined Military Hospital Rawalpindi - Rehman, Atiq-ur-; Ahmad, Riaz; Nadeem, Muhammad; Umair Tufail; Amjad Khan; Fayyaz Hussain (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the frequency and factors related to the presence of 17p deletion among patients diagnosed with chronic lymphocytic leukaemia at the Oncology Department of Combined Military Hospital Rawalpindi Study Design: Cross-sectional study. Setting And Duration Of Study: Oncology Department, Combined Military Hospital, Rawalpindi Pakistan, Feb 2020 to Mar 2021. Methodology: Patients with Chronic lymphocytic leukaemia were recruited for the study. The fluorescence in situ hybridization method was used to look for the presence of 17p deletion, using 10% cells as a cut-off value. Demographics, treatment status, and β2-microglobulin levels were correlated with 17p deletion in our study population. Results: A total of 102 patients diagnosed with Chronic Lymphocytic leukaemia were included in the analysis. The mean age of the patients was 55.82±7.176 years.74(72.5%) were male, while 28(27.5%) patients diagnosed with this condition were female. 17p deletion was present in 16(15.7%) patients, while 86(84.3%) patients were not detected with 17p deletion. Elevatedβ2-microglobulin levels were strongly related to 17p deletion in our target population (p-value-0.005). Conclusion: 17p deletion was a fairly common finding among patients of chronic lymphocytic leukaemia presenting to our department. Patients with elevated β2-microglobulin levels were more at risk of having this genetic mutation than those with normal β2-microglobulin levels.